Gothic Trouble: Cormac McCarthy’s The Road and the Globalized Order - Liénard-Yeterian, Marie (Text Matters: A Journal of Literature, Theory and Culture, 2016)
The article explores the way American author Cormac McCarthy uses the Gothic genre in his novel The Road as a means to address what has been called “our globalized order,” in particular the way it has turned human beings into consuming or consumed entities. Some dimensions of this globalized order indeed involve the reintroduction of slavery through human trafficking, unprecedented greed and labor capitalism, surveillance and personal data gathering. Hannah Arendt notes in The Origin of Totalitarianism that the disasters of the twentieth century had proved that a globalized order might “produce barbarians from its own midst by forcing millions of people into conditions which, despite all appearances, are the conditions of savages.” The artist’s task is to find the right language and images to address the breaking of the world. French philosopher J. P. Dupuy, for example, has argued that the financial world is a way to contain (contenir) the violence of competition, placing it into acceptable (symbolic) forms away from primal physical competition. McCarthy’s graphic use of Gothic tropes—including cannibalism, the wild forest, the haunted house, the chase, the conflict between light and darkness, the blurring of boundaries between different categories—creates a shock. The article also addresses the larger question of the impact of globalization on Gothic literature, and the impact of Gothic literature on real world matters as it contributes to and reflects upon and challenges global regimes of economic, social and economic power. In other words, what is the cultural work that the Gothic does in the present?